2003
DOI: 10.1021/ol0344265
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid-Induced Intramolecular Friedel−Crafts Cyclization of 1,3-Bis-exocyclic Dienes. A New Route to 4a-Methyltetrahydrofluorenes

Abstract: [reaction: see text] An efficient new method for constructing the 4a-methyltetrahydrofluorene skeleton was achieved via Friedel-Crafts intramolecular cyclization of 1,3-bis-exocyclic dienes. This strategy offers a simple and promising method for accessing complex structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Activation of the alkyne upon coordination to the electrophilic metal19, 21 launches a tosylate migration with a concomitant 1,2‐shift of R 1 that is followed by loss of a proton and a subsequent protiodemetalation to furnish the diene A 14. 22 Next, electrophilic activation of the conjugated diene23 yields a stabilized carbocation B that enters the first electrophilic aromatic substitution event. The resulting cycloisomerization process would render the conversion of 1 into C , which could then further evolve under the reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the alkyne upon coordination to the electrophilic metal19, 21 launches a tosylate migration with a concomitant 1,2‐shift of R 1 that is followed by loss of a proton and a subsequent protiodemetalation to furnish the diene A 14. 22 Next, electrophilic activation of the conjugated diene23 yields a stabilized carbocation B that enters the first electrophilic aromatic substitution event. The resulting cycloisomerization process would render the conversion of 1 into C , which could then further evolve under the reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…[58] A different approach to the intramolecular aromatic alkylation was proposed by Balme and co-workers, who investigated the catalytic Friedel-Crafts cyclization of aryl dienes 63. [59] Here, a series of 4a-methyltetrahydrofluorenes 65 were isolated in moderate to good yield (60-97 %) by employing Sc(OTf) 3 (20 %) in the cyclization of 1,3-bis-exocyclic dienes 63 (Scheme 22). Postulated intermediates of the process could be the electrophilically activated exomethylene species 64a or the conjugate carbocation 64b induced by the metal triflate.…”
Section: Cyclization Of Aryl Alkenesmentioning
confidence: 99%
“…A wide range of Lewis acids have been tested in this reaction and it was found that a catalytic amount of Sc(OTf) 3 allowed this reaction to proceed. 23 The method was applied to compounds 7b, 15b, 16b and 17b, and was very efficient for constructing the 4a-methyltetrahydrofluorene skeleton 24 that bears electron-donating substituents, an uncommon structure present in some recently isolated natural products 24 (Scheme 7).…”
Section: Intramolecular Friedel-crafts Reactionmentioning
confidence: 99%